2020
DOI: 10.7759/cureus.9725
|View full text |Cite
|
Sign up to set email alerts
|

A Rare Complication of Myocardial Infarction: Ventricular Septal Defect

Abstract: Ventricular septal defect (VSD) is a rare but lethal complication of myocardial infarction. We present a case of a 65-year-old male who presented with a history of progressive shortness of breath associated with productive cough. Physical examination was significant for crepitation in both lower lung fields and bilateral lower extremity edema. Chest X-ray revealed bilateral reticular opacities with small bilateral pleural effusions. Polymerase chain reaction (PCR) for COVID was positive. Echo showed a left ven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“… 4,5 It has been shown that post-infarction VSD complicates approximately 1–2% of cases of acute MI. 6,7 VSD occurs an average of 2–3 days after the infarction, but may occur any time in the first 2 weeks. 8 Septal rupture, with interventricular left to right shunt, can lead to right ventricular failure, pulmonary edema until biventricular failure.…”
Section: Discussionmentioning
confidence: 99%
“… 4,5 It has been shown that post-infarction VSD complicates approximately 1–2% of cases of acute MI. 6,7 VSD occurs an average of 2–3 days after the infarction, but may occur any time in the first 2 weeks. 8 Septal rupture, with interventricular left to right shunt, can lead to right ventricular failure, pulmonary edema until biventricular failure.…”
Section: Discussionmentioning
confidence: 99%
“… 1 VSR typically occurs within 1 week after the initial infarction without reperfusion. 1 2 5 With reperfusion (either thrombolysis or percutaneous coronary intervention), the median time from infarction to rupture is around 24 to 48 hours. 1 2 Although thrombolytic therapy may decrease the size of the infarct, it can also result in hemorrhage into the myocardium, which can accelerate the onset of the rupture.…”
Section: Discussionmentioning
confidence: 99%
“… 3 Although initially preferred for patients who are poor surgical candidates, percutaneous closure is becoming a more viable and less invasive treatment option for VSR as a definitive strategy or bridge to surgery. 4 5 The timing of surgical or percutaneous intervention remains debatable, with studies suggesting that delaying intervention results in lower mortality rates. 3 5 8 Patients who underwent surgery within 7 days of VSR onset had a 54.1% mortality compared with 18.4% mortality if delayed after 7 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Post-MI VSDs are most commonly caused by an occlusion of the left anterior descending artery. However, occlusion of any vessels that provide septal branches, without the presence of collaterals, has the potential to form a VSD [1][2]. Depending on the severity, the lack of perfusion to the interventricular septum during an MI results in tissue destruction and the possible formation of a septal defect [3].…”
Section: Introductionmentioning
confidence: 99%